Community knowledge, attitude and practices regarding malaria and long-lasting insecticidal nets in Churachandpur, Manipur - Marak, Rikrak Ch; Singh, T. Achouba (International Journal Of Community Medicine And Public Health, 2021)
Background: The disease is endemic in many parts of India, especially in the North- Eastern region. A study was done on head of the family’s knowledge, attitude and practice regarding malaria and long-lasting insecticidal bed nets and to determine the association between socio-demographic profile and knowledge and attitude. Methods: A cross-sectional study was conducted in the communities from 3 subcentres namely Pearsonmun, Thingkhangpai and Soipum under Saikot PHC, Churachandpur district of Manipur. House to house survey was carried out and only those who are eligible were interviewed using structured questionnaire. Random sampling and PPS was carried out to select the households head. SPSS was used for analysis. Results: Total of 289 heads of the family was interviewed. The total adequate knowledge score was 30.6% and only 26.3% had favourable attitude towards malaria and long-lasting insecticidal bed nets. There was significant association between marital status, educational qualification, occupation and monthly income with adequacy of knowledge. There was significant association between religion and attitude. Conclusions: Majority of the participants still lacks knowledge and attitude towards the malaria and long-lasting insecticidal nets (LLIN). IEC and awareness campaign should be carried out intensively and further study to be done to see the improvement of knowledge.